2016
DOI: 10.1177/0018726716676323
|View full text |Cite
|
Sign up to set email alerts
|

Beneath the white gaze: Strategic self-Orientalism among Chinese Australians

Abstract: This article analyses the ethno-cultural identities of Chinese Australian professionals through a postcolonial lens. Drawing on in-depth interviews with 21 participants, it explores how they engaged in self-Orientalism; casting themselves as exotic commodities for the benefit of white people and institutions. In particular, they enacted Chinese stereotypes through ‘mythtapping’ and ‘mythkeeping’ in order to secure recognition under the white gaze. As mythtappers, professionals presented themselves as custodian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 57 publications
1
47
0
Order By: Relevance
“…However, H3 is rejected. As a matter of fact, Chinese people do not accept the philanthropy or different exercises of this sort (Liu, ). They just accept and trust in their local government (Zhao & Hu, ).…”
Section: Results and Findingsmentioning
confidence: 99%
“…However, H3 is rejected. As a matter of fact, Chinese people do not accept the philanthropy or different exercises of this sort (Liu, ). They just accept and trust in their local government (Zhao & Hu, ).…”
Section: Results and Findingsmentioning
confidence: 99%
“…For instance, in a study of Moroccan and Turkish female Muslim entrepreneurs in the Netherlands, Essers and Benschop () found that informants had to negotiate multiple conflicting demands coming from their religion, culture, and work. Similarly, Liu () articulated how Chinese Australian professionals played into their ethno‐cultural identities by presenting themselves as exotic commodities, which helped them gain recognition with their White colleagues. There is less research on identity work concerning other social categories at work such as sexual identity.…”
Section: Methodology and Definitionsmentioning
confidence: 99%
“…While Said's work has primarily been applied to explore the discursive realm of international business and its representational practices, scholars have for some time pointed to a need for analyses of orientalism to also show its roles and expressions in the material realm (Srinivas 2013). Studies addressing such calls show how the orientalist discourse allows Western business leaders to understand themselves as ideals to be copied (McKenna 2011) but also how migrant professionals 'self-orientalise' to establish a role for themselves (Liu 2017).…”
Section: Framework: Neo-colonial Dynamics In Postcolonial Encountersmentioning
confidence: 99%